Influence of temperature on analog/radio frequency appearances of heterojunction cylindrical gate tunnel FETs - Singh P.K.; Baral K.; Singh A.K.; Tripathy M.R.; Upadhyay R.K.; Singh A.P.; Jit S. (My University, 2025)
Based on 3-D numerical simulation, we have presented the influence of temperature on the analog (such as drain current (I{d}), transconductance (g{m}), subthreshold swing (SS), I{ON}/I{OFF} ratio, transconductance generation factor (TGF), and gate leakage (I{g})) and radio frequency parameter (such as gate capacitance (C{gg}), cut-off frequency (f{t}), and gain-bandwidth product (GBW) of heterojunction (HJ) cylindrical gate (CG) tunnel field-effect transistors (TFETs). From the simulation results, it is observed that almost no change in ON-state current (I{ON}) while OFF-state current (I{OFF}) changed rapidly for the whole range of temperature (250K to 450K). Further, rapid change is observed in the C{gg}, f{t}, and GBW at a larger gate voltage while almost constant at smaller gate voltage (V{text{GS}} < 0.5mathrm{V}). © 2020 IEEE.